RESEARCH OF GUNSHOT PRODUCTS USING X-RAY FLUORESCENCE ANALYSIS - DOTSENKO, OLEH; SHELESTIUK, OLEKSANDR; ANTONIUK, OLEKSANDR; STREMETSKYI, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Detection and research of gunshot products using modern devices and research methods is an urgent scientific and practical task. In the literary sources, it is proposed to use X-ray fluorescence analysis, electron microscopy, and optical emission spectroscopy in forensics both to study the product of the shot and to determine the composition of gunpowder and other elements of the charge.The aim of the presented work was to establish the dependence of the nature of the shot products on the composition of the charge elements and the distance to the target using X-ray fluorescence analysis. The composition of the charge elements should be understood as the chemical composition of the powder charge, capsule charge, casing material and the material of the bullet or its shell.As a result of the use of X-ray fluorescence analysis to establish the dependence of the nature of the shot products on the composition of the charge elements and the distance to the target, processing and analysis of the obtained results, a number of conclusions can be drawn.The Elvax Pro device for X-ray fluorescence analysis can be used to study the products of the shot and establish the regularity of the distribution of elements depending on the distance. Studies have shown that the composition of the shot products practically does not depend on the composition of the powder charge, which is explained by the small concentration of modifying elements that are in the organic matrix, but it depends on the capsule charge and the material of the surface of the bullet that was used for the shot. The established dependence of the distribution of the radiation intensities of the elements that are part of the shot products on the distance makes it possible to establish the distance from the weapon to the target. The best marker for determining the distance to the target using X-ray fluorescence analysis due to its sufficiently high content in the shot products is lead.
Keywords: X-ray fluorescence analysis; gunpowder; shot products; capsule charge